Pengaruh Profitabilitas, Kebijakan Dividen, dan Struktur Modal pada Nilai Perusahaan - Yadnya Dewi, Ni Kadek Puspita; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2019)
The purpose of this study is to know empirically the effect of profitability, dividend policyi andi capital structure on thei value of LQ45 companiesi listedi oni thei Indonesiai Stocki Exchangei for the periodi 2014-2018. Samplesi werei selectedi usingi purposive samplingi techniquei to obtaini a totali samplei of six companies, so the numberi of observationsi with a studyi period of 5 years was 30 observations. Total populations were sixtyeight companies. The data analyse technique used is multiple linear regression analysis. Based on the analysis that has been done shows that the probability, dividend policy and capital structure significant positive effect on value of the company . Keywords : Profitability; Dividend Policy; Capital Structure; Company Value